Kontribusi kekuatan Otot Lengan dan Kelentukan Pergelangan Tangan Terhadap Kemampuan Servis Panjang Permainan Bulutangkis Siswa SMP Negeri 11 Makassar - Andi Sahrul Jahrir; Achmad Karim; Andrew Joshua (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2021)
This research aims to determine: (1) Is there a contribution of arm muscle strength to the long serve ability of the 11 Makassar public junior high school students' badminton game (2) Is there a contribution of wrist flexibility to the long serve ability of the 11 Makassar public junior high school students' badminton game ability (3) Is it there is a joint contribution of arm muscle strength and wrist flexibility to the long serve ability of the students of SMP Negeri 11 Makassar. This type of research is a correlational research. With quantitative research methods or the way the sample is taken, namely by means of a simple random sampling technique. Data collection techniques are tests and measurements. The population in this study were students of SMP Negeri 11 Makassar. The sample used was 30 male students. The data analysis techniques used in this study were descriptive analysis, correlation analysis, and regression analysis at a significant level of = 0.05 through the SPSS 21 program. The results showed that: (1) There was a significant contribution of arm muscle strength to the long serve ability of students' badminton games. Makassar State Junior High School 11 Makassar with a value of r = 0.747 (ρ < = 0.05; (2) There is a significant contribution of wrist flexibility to the long service ability of badminton players of State Junior High School 11 Makassar with a value of r = 0.547 (ρ < = 0.05; (3) There is a jointly significant contribution of arm muscle strength and wrist flexibility to the long-serving ability of the badminton players of SMP Negeri 11 Makassar with a regression value (R) = 764 determinant coefficient (